Effects of a Family Participation Promotion Program on Medication Adherence in Muslim Elderly Patients with Myocardial Infarction: A pilot Study - Datae, Ameenoh; Perngmark, Pajongsil; Boonyasopun, Umaporn (Princess of Naradhiwas University Journal, 2024)
The purpose of this study was to determine the effect of a family participation promotion program on medication adherence in Muslim elderly patients with myocardial infarction. Research’s methodology: A pilot study. Twelve patients with myocardial infarction and family members (six pairs) were used as study samples. They were selected based on predetermined criteria and received the program. Medication adherence behavior questionnaires for patients with myocardial infarction and family member participation questionnaires were utilized to collect data. All questionnaires were validated by three experts. Alpha’s Cronbach’s reliability results were 0.95 and 0.93, respectively. Twenty samples that were comparable to the research sample were used to test the reliability of the questionnaires. Personal data were analyzed by using descriptive statistics including frequency, percentage, mean, standard deviation, and the assumptions of the Wilcoxon sign test. The findings showed that the mean scores for medication adherence and family member participation of Muslims elderly patients with myocardial infarction after receiving program were statistically significantly higher than before receiving the program. (Z= -2.20 and -2.21, p < .05) The results indicated that a family participation promotion program can enhance caring of Muslims elderly patients with myocardial infarction by encouraging family members to assist in providing continuous long-term care. The program’s impact on other health-related behaviors should also be assessed in patients with other diseases.